Nanotechnology-Based Drug Delivery Systems for Melanoma Antitumoral Therapy: A Review. (11th May 2015) - Rigon, Roberta Balansin; Oyafuso, Márcia Helena; Fujimura, Andressa Terumi; Gonçalez, Maíra Lima; Prado, Alice Haddad do; Gremião, Maria Palmira Daflon; Chorilli, Marlus
Abstract : Melanoma (MEL) is a less common type of skin cancer, but it is more aggressive with a high mortality rate. The World Cancer Research Fund International (GLOBOCAN 2012) estimates that there were 230, 000 new cases of MEL in the world in 2012. Conventional MEL treatment includes surgery and chemotherapy, but many of the chemotherapeutic agents used present undesirable properties. Drug delivery systems are an alternative strategy by which to carry antineoplastic agents. Encapsulated drugs are advantageous due to such properties as high stability, better bioavailability, controlled drug release, a long blood circulation time, selective organ or tissue distribution, a lower total required dose, and minimal toxic side effects. This review of scientific research supports applying a nanotechnology-based drug delivery system for MEL therapy.